2013
DOI: 10.1111/jocn.12379
|View full text |Cite
|
Sign up to set email alerts
|

Life after critical illness: an overview

Abstract: What seems clear is the need for a co-ordinated, multidisciplinary, designated recovery and rehabilitation pathway that begins as soon as the patient is admitted into an intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 77 publications
0
28
0
2
Order By: Relevance
“…1,2 A systematic review 1 of 21 studies with a total of 7320 adult medical and surgical ICU survivors followed up for at least 6 months after discharge indicated that HRQOL was reduced in almost all assessed domains. The HRQOL often was lower than the patients' HRQOL before the index critical illness.…”
Section: Contrast the Health-related Quality Of Life (Hrqol)mentioning
confidence: 99%
“…1,2 A systematic review 1 of 21 studies with a total of 7320 adult medical and surgical ICU survivors followed up for at least 6 months after discharge indicated that HRQOL was reduced in almost all assessed domains. The HRQOL often was lower than the patients' HRQOL before the index critical illness.…”
Section: Contrast the Health-related Quality Of Life (Hrqol)mentioning
confidence: 99%
“…For some patients, the recognition of the significant burden that critical illness had placed on family members required personal counselling. In the UK National Institute for Health and Care Excellence (NICE) Clinical Guideline 83, ‘Rehabilitation after critical illness’ was published in March ; however, there is a general consensus that this has not been embedded or resourced effectively or consistently (Cotton, ; Rattray, ). This is despite the subsequent studies (Ohtake et al , ) reinforcing the requirement for early rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing documentation of patients' sleep in AGCCUs has been reported by Ritmala‐Castren et al () as being poor, consistently overestimating the volume of sleep and unable to assess sleep quality. Sleep deprivation augments the well‐documented fatigue that patients experience post‐discharge from critical care (Cutler et al , ; Rattray, ; Misak, and others).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations